Prevention of Postsurgical Lymphedema by 9-cis Retinoic Acid. Issue 2 (August 2016) - Bramos, Athanasios; Perrault, David; Yang, Sara; Jung, Eunson; Hong, Young Kwon; Wong, Alex K.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To determine the effect of 9- cis retinoic acid (9- cis RA) on postsurgical lymphedema. Background: 9- cis RA promotes lymphangiogenesis in vitro and in vivo and has promise as a therapeutic agent to limit the development of postsurgical lymphedema. Methods: Lymphedema was induced in the right hind limb after a single fraction of 20 Gy radiation, popliteal lymphadenectomy, and lymphatic vessel ablation. Postoperatively, mice were randomly divided in to 2 groups that received daily intraperitoneal injections of either (1) an oil-based vehicle solution (control) or (2) 0.08 mg/kg of 9 -cis RA dissolved in a vehicle solution. Outcome measures included paw thickness, lymphatic drainage, and lymphatic vessel density as measured by podoplanin immunohistochemistry and whole mount skin analysis. Results: Using our combined injury protocol, postsurgical lymphedema was observed 89% of the time. 9- cis RA-treated animals had less early postsurgical edema and significantly less paw lymphedema compared with vehicle-treated animals at all time-points ( P < 0.001). 9 -cis RA-treated animals had significantly faster lymphatic drainage as measured by indocyanine green clearance and increased lymphatic vessel density as measured by podoplanin immunohistochemistry ( P < 0.001) and whole mount skin analysis ( P < 0.05). Conclusions: We have developed a highly reproducible model of secondary lymphedema and have demonstrated that 9 -cis RA significantly prevents postsurgical lymphedema. Treatment with 9- cis RA is associated with increased lymphatic clearance and lymphangiogenesis. Because 9 -cis RA (alitretinoin) is already approved for clinical use by the US Food and Drug Administration for other conditions, it has the potential to be repurposed as a preventative agent for postsurgical lymphedema in humans.